2020
DOI: 10.3389/fendo.2019.00921
|View full text |Cite
|
Sign up to set email alerts
|

Role of the End-Point Mediators of Sympathoadrenal and Sympathoneural Stress Axes in the Pathogenesis of Experimental Autoimmune Encephalomyelitis and Multiple Sclerosis

Abstract: The role of stress effector systems in the initiation and progression of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE), the most commonly used experimental model of MS, has strongly been suggested. To corroborate this notion, alterations in activity of the sympathoadrenal and sympathoneural axes of sympathoadrenal system (a major communication pathway between the central nervous system and the immune system), mirrored in altered release of their end-point mediators (adrenaline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 138 publications
0
6
0
Order By: Relevance
“…3). Indeed, we have shown that β-adrenoceptor blockade reduces the incidence and severity of EAE [294][295][296].…”
Section: Influence Of Aging On Mechanisms Controlling the Development...mentioning
confidence: 95%
“…3). Indeed, we have shown that β-adrenoceptor blockade reduces the incidence and severity of EAE [294][295][296].…”
Section: Influence Of Aging On Mechanisms Controlling the Development...mentioning
confidence: 95%
“…Furthermore, cells regulating innate immunity and T lymphocytes can secrete noradrenaline that may be involved in a local autocrine and paracrine self-amplifying feed-forward loop enhancing proinflammatory cytokines synthesis by myeloid cells and inflammatory damage in experimental autoimmune encephalomyelitis (EAE) and in multiple sclerosis (MS). All cell types involved in the autoimmune inflammation and targeted tissue damage in autoimmune central nervous system diseases express receptors for catecholamines [4]. Catecholamines exert most of their immunomodulatory actions through β 2 -adrenoreceptors; however, α-adrenoreceptors can play a role in the diseases [4].…”
Section: A Strict Dialog Among Neurotransmitters Hormones and Cytokinesmentioning
confidence: 99%
“…All cell types involved in the autoimmune inflammation and targeted tissue damage in autoimmune central nervous system diseases express receptors for catecholamines [4]. Catecholamines exert most of their immunomodulatory actions through β 2 -adrenoreceptors; however, α-adrenoreceptors can play a role in the diseases [4].…”
Section: A Strict Dialog Among Neurotransmitters Hormones and Cytokinesmentioning
confidence: 99%
“…In autoimmune diseases, catecholamines modulate disease states in a phase-dependent manner. For example, in an experimental autoimmune encephalomyelitis (EAE) model, NE acts differently in the central and peripheral nervous systems at the induction and effector phases [ 36 ]. In the induction phase, β2-adrenergic signaling promotes microglial inflammation at spinal cord while suppresses CD4 + T-cell proliferation and skewing toward Th17 at the draining lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…In the induction phase, β2-adrenergic signaling promotes microglial inflammation at spinal cord while suppresses CD4 + T-cell proliferation and skewing toward Th17 at the draining lymph nodes. In the effector phase, α1-adrenergic signaling activates microglia, macrophages, and dendritic cells and suppresses regulatory T-cell responses at both sites [ 36 ]. Chronic cold-stress stimulation ameliorates neuroinflammation by suppressing antigen presentation by monocytes in the bone marrow via β3-adrenergic receptor signaling [ 37 ].…”
Section: Introductionmentioning
confidence: 99%